The Role Of The Discovery Strategy In Developing Scientific Concepts (Health And Physical) Among Kindergarten Children From The Point Of View Of Teachers (A Field Study In The Governorate Of Damascus) (Damascus University Journal of educational and Psychologyical sciences, 2024)
The role of the discovery strategy in developing scientific concepts (health and physical) among kindergarten children from the point of view of teachers  (A field study in the governorate of Damascus)The research aims to identify the role of the discovery strategy in developing scientific concepts (health and physical) among kindergarten children from the point of view of teachers, the researcher followed the descriptive and analytical approach, and the research sample consisted of (129) female teachers of the third category.The most important findings of the research : -The role of the discovery strategy in developing scientific concepts from the female teachers’ point of view, For health concepts, it is an average role,  For the physical concepts, it is a weak role, for the scientific concepts of the resolution as a whole, it is an average role.- There are statistically significant differences between the average scores of the research sample members on identifying the role of discovery learning strategy in developing scientific concepts according to the variable numberof training courses.- There are no statistically significant differences between the average scores of the research sample members on the identification of the role of discovery learning strategy in developing scientific concepts according to the variable number of years of experience.- There are statistically significant differences between the mean scores of the research sample members on identifying the role of discovery learning strategy in developing scientific concepts according to the academic qualification variable.
Keywords: Discovery Strategy; Scientific Concepts